Electrophoretic deposition of titanate nanotube films with extremely large wetting contrast - Lai, Yuekun (2012)
A facile electrophoretic deposition (EPD) process has been developed to prepare thin films consisting of titanate nanotubes (TNTs) that were synthesized by a hydrothermal approach. Such an EPD process offers easy control in the film thickness and the adhesion to the substrate was found to be strong. The chemical composition and structure of the products have been characterized by XRD, HRTEM, and FESEM. It was found that the functionalization of TNTs plays a key role on the electrolyte stability and the formation of a uniform TNT film with good adhesion. The as-prepared TNT films show exceptional superhydrophilic behavior with ultra-fast spreading, while it converts to superhydrophobicity yet with strong adhesion after 1H,1H,2H,2H-perfluorooctyl-triethoxysilane modification. This study provides an interesting method to prepare films with extremely high wettability contrast that are useful for producing different types of functional materials.